2000
DOI: 10.1007/s11661-000-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

The 900 °C isothermal section of Ti-Ni-V alloys

Abstract: The AB 2 -type Ni-based alloys are the most prominent candidates as electrode materials in the recent development of Cd-free rechargeable batteries. [1] Most of these developing AB 2 alloys are multicomponent alloys, and the Ti-Ni-V ternary system is one of the most important base systems for the AB 2 electrode alloys. The three constituent binary systems, Ti-V, Ni-Ti, and Ni-V, have been studied earlier. [2,3,4] Ti-V is an isomorphous system with a continuous solid solution at high temperatures and there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…In addition, the Sn-Zn alloys examined in this study exhibited a higher enthalpy of fusion in comparing with eutectic Sn-Pb and Sn-Ag solders. 19) The cooling curves of the specimens, Fig. 7, indicate that all the samples show a eutectic feature and no inflection point above the eutectic temperature.…”
Section: Microstructural Featuresmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the Sn-Zn alloys examined in this study exhibited a higher enthalpy of fusion in comparing with eutectic Sn-Pb and Sn-Ag solders. 19) The cooling curves of the specimens, Fig. 7, indicate that all the samples show a eutectic feature and no inflection point above the eutectic temperature.…”
Section: Microstructural Featuresmentioning
confidence: 87%
“…25) At a small addition of Ga (less than 0.25 mass%), Ga atoms tend to segregate at the cell boundary regions. The segregation of Ga breaks up the interface between the cells and Enthalpy of fusion, h/J/g 0Ga 0.5Ga 1.0Ga 1.8Ga Sn-Ag [19] Sn-Pb [19] Sn-Zn [11] (b) A further increase in Ga content converts the eutectic structure to a part-normal and part-irregular structure. This phenomenon is attributed to the composition variation of the solidification front.…”
Section: Formation Of the Normal-irregular Structure Of Snzn-ga Alloysmentioning
confidence: 99%
“…4 C respectively, which are very close to the previous published results. 16,22) When 0.5 mass% Ag is added to the Sn-9Zn solder alloy, the T onset of the solder alloy increases from 195. 5 to 196.7 C and the increment of 1.2 C is acceptable.…”
Section: Thermal Properties Of the Solder Alloysmentioning
confidence: 99%
“…Chen et al 16) have demonstrated that the Sn-37Pb solder alloy melts at 183 C and the enthalpy of fusion is 45.2 J/g. The melting point of the solder alloy reported by Chen et al 16) is close to our result, but the fusion heat is only one half of ours, because the K value of the DSC instrument has not been calibrated in the former study.…”
Section: Thermal Properties Of the Solder Alloysmentioning
confidence: 99%
See 1 more Smart Citation